Sistem Pendukung Keputusan Pemilihan Pegawai Teladan Menggunakan Metode Weight Product Berbasis Web Pada Klinik Bersalin Harapan Kami Pandeglang - Parid Amarullah; Ayu Mira Yunita; Aghy Gilar Pratama; Robby Rizky (Admin Situstika, 2024)
The selection of Exemplary Employees at the Harapan Kami Maternity Clinic Pandeglang currently still has obstacles, including the length of the employee selection process so that it takes a very long time. The selection process is so strict in accordance with the criteria of Employee Attendance, Employee Performance, Employee Skills at Work, Ethics and Manners. Because the selection of exemplary employees is not easy with the criteria that must be met by each employee, in this case it raises a problem which includes, The lack of data capture because it is still in manual form, always relying on assessments based on employees' daily opinions not based on the fact of employee performance in the field and finally there is still a rampant selection based on emotional closeness or nepotism in the selection of exemplary employees in the Maternity Clinic Our hope is pandeglang. The purpose of this study is to Design a Decision Support System for the selection of Exemplary Employees using the Web-Based Weight Product Method to provide information effectively and efficiently with decision making by the Leadership. This research uses the Weighted Product (WP) method, to qualify the criteria as an exemplary employee, namely the criteria for Employee Attendance, Employee Performance, Employee Skills at Work, Ethics and Manners., The results of this study formed a decision support system that can process data into consideration. The selection of exemplary employees will be used as input which is then the calculation process using the Weighted Product(WP) Method. The results of this system result in the cracking of alternatives as recommendations for decision-makers for elections. This method is expected to help the Head of Administration and Head of Clinic to determine Exemplary Employees quickly and accurately, so that decision making on the selection of exemplary employees is more targeted for Exemplary Employees who deserve awards